Maintaining and troubleshooting your 3D printer - Bell, Charles (Technology in action series., 2014)
Maintaining and Troubleshooting Your 3D Printer by Charles Bell is your guide to keeping your 3D printer running through preventive maintenance, repair, and diagnosing and solving problems in 3D printing. If you?ve bought or built a 3D printer such as a MakerBot only to be confounded by jagged edges, corner lift, top layers that aren?t solid, or any of a myriad of other problems that plague 3D printer enthusiasts, then here is the book to help you get past all that and recapture the joy of creative fabrication. The book also includes valuable tips for builders and those who want to modify their printers to get the most out of their investment. Good fabrication begins with calibration. Aligning the print bed to support deposition of medium in three dimensions is critical. Even off-the-shelf machines that are pre-built must be aligned and periodically realigned throughout their life cycle. Maintaining and Troubleshooting Your 3D Printer helps you achieve and hold proper alignment. Maintaining and Troubleshooting Your 3D Printer also helps with software and hardware troubleshooting. You?ll learn to diagnose and solve firmware calibration problems, filament and feed problems, chassis issues, and more. Finally there are regular maintenance and enhancements. You?ve invested significantly in your 3D printer. Protect that investment using the guidance in this book. Learn to clean and lubricate your printer, to maintain the chassis, and know when realignment of the print bed is needed. Learn ways to master your craft and improve the quality of your prints through such things as post-print finishing and filament management. Don?t let the challenges of 3D printing stand in the way of creativity. Maintaining and Troubleshooting Your 3D Printer by Charles Bell helps you conquer the challenges and get the most benefit from your expensive investment in personal fabrication.